Multiple territories and hybrids crossovers in an in situ artistic experience - Poll, Maria das Graças Garcia (2015)
The present Visual Poetry research about technology art envolves the multiple territories issues starting from the intersection of singular spaces, characterized by specific languages in analog and digital media, generating the reconfiguration of hybrid spaces that comes from the flows and the meetings of diverse artistic practices. Based on previous experience in artistic collectivity, linked to issues of production in art and occupation of non-institutionalized spaces in the city, the study leads to experiencing proposals in situ for a local/a depositary place of memories and experiences resulting from this trajectory. Referring to the cultural environment of the city and its history, we tried to propose the generation of a new perceptual capability for that space, through the collectivity participation, which are also relevant in this study. The installation is characterized by a temporarily displayed work. This work s presentation takes place in ephemeral and transitory space-time relation ship. The conduct of the research was based on authors as Carvalho (2005); Haesbaert (2004); Plaza (1998); Santos (1991); Cauquelin (2007); Bourriaud (2009); Barros (1998, 1999), the approach of the concepts